Cisplatin induced sensory neuropathy is prevented by vascular endothelial growth factor-A - Vencappa, Samanta; Donaldson, Lucy F.; Hulse, Richard P. (E-Century Publishing, 2015)
Increased patient survival is a mark of modern anti-cancer therapy success. Unfortunately treatment side-effects such as neurotoxicity are a major long term concern. Sensory neuropathy is one of the common toxicities that can arise during platinum based chemotherapy. In many cases the current poor understanding of the neurological degeneration and lack of suitable analgesia has led to high incidences of patient drop out of treatment. VEGF-A is a prominent neuroprotective agent thus it was hypothesised to prevent cisplatin induced neuropathy. Systemic cisplatin treatment (lasting 3 weeks biweekly) resulted in mechanical allodynia and heat hyperalgesia in mice when compared to vehicle control. PGP9.5 sensory nerve fibre innervation was reduced in the plantar skin in the cisplatin treated group versus vehicle control mice. The cisplatin induced sensory neurodegeneration was associated with increased cleaved caspase 3 expression as well as a reduction in Activating Transcription Factor 3 and panVEGF-A expression in sensory neurons. VEGF-A165b expression was unaltered between vehicle and cisplatin treatment. rhVEGF-A165a and rhVEGF-A165b both prevented cisplatin induced sensory neurodegeneration. Cisplatin exposure blunts the regenerative properties of sensory neurons thus leading to sensory neuropathy. However, here it is identified that administration of VEGF-A isoform subtypes induce regeneration and prevent cell death and are therefore a possible adjunct therapy for chemotherapy induced neuropathy.